Aminated Graphene Oxide as a Potential New Therapy for Colorectal Cancer. (20th March 2019) - Krasteva, Natalia; Keremidarska-Markova, Milena; Hristova-Panusheva, Kamelia; Andreeva, Tonya; Speranza, Giorgio; Wang, Dayong; Draganova-Filipova, Milena; Miloshev, George; Georgieva, Milena
Abstract : Nanotechnology-based drug delivery systems for cancer therapy are the topic of interest for many researchers and scientists. Graphene oxide (GO) and its derivates are among the most extensively studied delivery systems of this type. The increased surface area, elevated loading capacity, and aptitude for surface functionalization together with the ability to induce reactive oxygen species make GO a promising tool for the development of novel anticancer therapies. Moreover, GO nanoparticles not only function as effective drug carriers but also have the potential to exert their own inhibitory effects on tumour cells. Recent results show that the functionalization of GO with different functional groups, namely, with amine groups, leads to increased reactivity of the nanoparticles. The last steers different hypotheses for the mechanisms through which this functionalization of GO could potentially lead to improved anticancer capacity. In this research, we have evaluated the potential of amine-functionalized graphene oxide nanoparticles (GO-NH2 ) as new molecules for colorectal cancer therapy. For the purpose, we have assessed the impact of aminated graphene oxide (GO) sheets on the viability of colon cancer cells, their potential to generate ROS, and their potential to influence cellular proliferation and survival. In order to elucidate their mechanism of action on the cellular systems, we have probed their genotoxic and cytostatic properties and compared them to pristine GO. Our results revealed that both GO samples (pristine and aminated) were composed of few-layer sheets with different particle sizes, zeta potential, and surface characteristics. Furthermore, we have detected increased cyto- and genotoxicity of the aminated GO nanoparticles following 24-hour exposure on Colon 26 cells. The last leads us to conclude that exposure of cancer cells to GO, namely, aminated GO, can significantly contribute to cancer cell killing by enhancing the cytotoxicity effect exerted through the induction of ROS, subsequent DNA damage, and apoptosis.